Quantitative proteomic identification of host factors involved in the Salmonella typhimurium infection cycle - Kaloyanova, Dora; Vogels, Mijke; van Balkom, Bas W M; Helms, J Bernd (Humana Press, 2014)
Quantitative proteomics, based on stable isotope labeling by amino acids in cell culture (SILAC), can be used to identify host proteins involved in the intracellular interplay with pathogens. This method allows identification of proteins subject to degradation or upregulation in response to intracellular infection. It can also be used to study intracellular dynamics (trafficking) of proteins in response to the infection. Here, we describe the analysis of changes in protein profiles determined in Golgi-enriched fractions isolated from cells that were either mock-infected or infected with Salmonella typhimurium. Using the SILAC approach we were able to identify 105 proteins in Golgi-enriched fractions that were significantly changed in their abundance as a result of Salmonella infection.
Keywords: Host–pathogen interactions; Salmonella typhimurium; SILAC; Cellular fractionation; Golgi membrane enrichment; Taverne